The anxiety level of healthcare professionals and hospital support staff during the COVID-19 pandemic : The anxiety level of healthcare workers - Salcan, Sara; Ezmeci, Talat (Journal of Surgery and Medicine, 2023)
Background/Aim: The coronavirus 2019 (COVID-19) pandemic has placed a significant psychological burden on healthcare professionals. This study aims to identify the anxiety levels of healthcare professionals and non-healthcare personnel during the pandemic. Methods: This cross-sectional study was conducted on healthcare professionals during the pandemic, and we attempted to reach all personnel without setting a specific sample size. Participants completed a survey that included demographic information and the State-Trait Anxiety Inventory (STAI). We compared anxiety scores and working conditions between healthcare and non-healthcare personnel during the pandemic. Results: Our study included 204 personnel, with 45.1% being healthcare professionals and 54.9% non-healthcare professionals. The mean state anxiety score for all participants was 44.7 (10.3). Female professionals, those working in intensive care, and personnel who believed they lacked sufficient protection training had significantly higher mean anxiety scores (P=0.001, P=0.006, P<0.001, respectively). Participants with mild or no problems initiating and maintaining sleep and waking up early had lower mean anxiety scores (P<0.001). There was no statistically significant difference between healthcare professionals and non-healthcare personnel in mean scores (P=0.59). Conclusion: Our study found that all personnel experienced medium-level anxiety during the pandemic, indicating an increased risk for hospital staff. The fact that non-healthcare personnel had similar anxiety scores to healthcare professionals highlights the need for psychosocial interventions to support all hospital staff, regardless of their role in patient care.